Strategi Pengelolaan Kelas Untuk Meningkatkan Kualitas Pembelajaran: Indonesia - Saputra, Andika (Universitas Muhammadiyah Surabaya, 2025)
Effective classroom management is the key to creating a conducive learning environment and supporting student success. This article discusses various classroom management strategies that educators can implement to improve the quality of learning. The main focus of this research is on the application of an approach based on active student participation, the formation of positive relationships between teachers and students, and the use of information technology to support the teaching and learning process. By implementing strategies such as setting clear rules, efficient time management, and providing constructive feedback, teachers can create a pleasant and productive classroom atmosphere. Apart from that, collaboration between students and parental involvement in the educational process is also considered important in increasing student motivation and learning outcomes. It is hoped that the results of this article can provide practical guidance for educators in designing and implementing better classroom management, as well as encouraging improvements in the quality of learning at various levels of educatio